Exploring gene tree incongruence at the origin of ants and bees (Hymenoptera). (18th December 2018) - Camacho, Gabriela P.; Pie, Marcio R.; Feitosa, Rodrigo M.; Barbeitos, Marcos S.
Abstract: The fact that different phylogenomic data sets can lead to highly supported but inconsistent results suggest that conflict among gene trees in real data sets could be severe. We provide here a detailed exploration of gene tree space to investigate the relationships in Hymenoptera based on data obtained by Johnson et al. ( Current Biology, 2013, 23, 2058), in which ants and Apoidea (bees and spheciform wasps) were recovered as sister groups, contradicting previous studies. We found high levels of topological variation among gene trees, several of them disagreeing with previously published hypotheses. To profile the dynamics of emerging support versus conflicting signal in combined analysis of data, we employed a novel method based on the incremental addition of randomized data to coalescence‐based phylogenetic inference. Although the monophyly of Aculeata and of Formicidae were consistently recovered using as little as 6.5% of the 308 available markers, signal for the Formicidae + Apoidea clade prevailed only after more than 50% of the loci were sampled. Still, non‐negligible support for alternative hypotheses remained until all genes were added to the analysis. Our results suggest that phylogenetic conflict is rather pervasive and not scattered as noise across individual gene trees because alternative topologies were recovered not from a specific subset, but from several random combinations of loci. Thus, even though phylogenetic signal recovered from full gene data sets was already dominant in much smaller ensembles, large amounts of data may be indeed necessary to overcome phylogenetic conflict.